Rationally Designed PI3Kα Mutants to Mimic ATR and Their Use to Understand Binding Specificity of ATR Inhibitors. Issue 11 (2nd June 2017) - Lu, Yipin; Knapp, Mark; Crawford, Kenneth; Warne, Robert; Elling, Robert; Yan, Kelly; Doyle, Michael; Pardee, Gwynn; Zhang, Li; Ma, Sylvia; Mamo, Mulugeta; Ornelas, Elizabeth; et al.
Abstract: ATR, a protein kinase in the PIKK family, plays a critical role in the cell DNA-damage response and is an attractive anticancer drug target. Several potent and selective inhibitors of ATR have been reported showing significant antitumor efficacy, with most advanced ones entering clinical trials. However, due to the absence of an experimental ATR structure, the determinants contributing to ATR inhibitors' potency and specificity are not well understood. Here we present the mutations in the ATP-binding site of PI3Kα to progressively transform the pocket to mimic that of ATR. The generated PI3Kα mutants exhibit significantly improved affinity for selective ATR inhibitors in multiple chemical classes. Furthermore, we obtained the X-ray structures of the PI3Kα mutants in complex with the ATR inhibitors. The crystal structures together with the analysis on the inhibitor affinity profile elucidate the roles of individual amino acid residues in the binding of ATR inhibitors, offering key insights for the binding mechanism and revealing the structure features important for the specificity of ATR inhibitors. The ability to obtain structural and binding data for these PI3Kα mutants, together with their ATR-like inhibitor binding profiles, makes these chimeric PI3Kα proteins valuable model systems for structure-based inhibitor design. Graphical Abstract: Highlights: ATR is an attractive anticancer drug target but no X-ray structure is available. Designed PI3Kα mutants to transform the ATP-binding site to mimic that of ATR. Resulting PI3Kα mutants exhibit improved affinity for selective inhibitors of ATR. Obtained crystal structures of the PI3Kα mutants in complex with ATR inhibitors Insights into the key binding and structural features for the ATR inhibitors